2022
DOI: 10.1096/fj.202101205rr
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of MAT2A suppresses osteoclastogenesis and prevents ovariectomy‐induced bone loss

Abstract: Methionine adenosyltransferase II alpha (MAT2A) is the key enzyme to transform methionine and adenosine‐triphosphate (ATP) to S‐adenosylmethionine (SAM), a general methyl‐group donor in vitro. MAT2A has been reported to participate in the NF‐κB pathway and maintain the methylated modification, which also affects osteoclastogenesis. In this study, we found the expression of MAT2A was increased upon RANKL stimulation. Pharmacological inhibition of MAT2A by its selective inhibitor AG‐270 or genetic silencing by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Abnormal metabolism of valine might serve as a key mechanism of OP (31,38,75) relationship between OP and amino acid metabolism was further explored. The results of the study indicate that the change of the metabolite glutamate may play an important role in the pathogenesis of OP (26,36,70).…”
Section: Amino Acid Metabolismmentioning
confidence: 92%
See 2 more Smart Citations
“…Abnormal metabolism of valine might serve as a key mechanism of OP (31,38,75) relationship between OP and amino acid metabolism was further explored. The results of the study indicate that the change of the metabolite glutamate may play an important role in the pathogenesis of OP (26,36,70).…”
Section: Amino Acid Metabolismmentioning
confidence: 92%
“…There is increasing evidence that some of the causative factors are modifiable risk factors for OP, such as abnormal drug intake, high fat, and abnormal hormone levels. Studies have shown that these substances can induce secondary OP by regulating changes in metabolite levels (32)(33)(34)(35)(36)(37)(38).…”
Section: Abnormal Metabolism In Opmentioning
confidence: 99%
See 1 more Smart Citation
“…F‐actin ring staining and pit formation assays were performed as described earlier to analyze the effect of FAAH inhibition on osteoclast function 30 . Briefly, BMMs were cultured on 0.2% collagen‐gel coated 6‐well plates with M‐CSF (30 ng/ml) and RANKL (75 ng/ml) until osteoclasts formed.…”
Section: Methodsmentioning
confidence: 99%
“…F-actin ring staining and pit formation assays were performed as described earlier to analyze the effect of FAAH inhibition on osteoclast function. 30 Briefly, BMMs were cultured on 0.2% collagen-gel coated 6-well plates with M-CSF (30 ng/ml) and RANKL (75 ng/ml) until osteoclasts formed. Subsequently, RANKL-induced mature osteoclasts were digested with type I collagenase (0.2%) and reseeded in Corning osteo assay strip wells, and stimulated with different concentrations of PF (0, 0.25, 0.5, 1, and 2.5 μM) or infected with the lentivirus carrying FAAH-specific shRNA or the control lentivirus for an additional 3 days in the presence of 75 ng/ml RANKL.…”
Section: F-actin Staining and Pit Formation Assaymentioning
confidence: 99%